Autoinflammatory syndromes: report on three cases - Matos, Thais Cunha; Terreri, Maria Teresa Ramos Ascensão; Petry, Daniela Gerent; Barbosa, Cássia Maria; Len, Claudio Arnaldo; Hilário, Maria Odete Esteves (São Paulo Medical Journal, 2009)
CONTEXT: Autoinflammatory syndromes are diseases manifested by recurrent episodes of fever and inflammation in multiple organs. There is no production of autoantibodies, but interleukins play an important role and acute-phase reactants show abnormalities. Our aim was to report on three cases of autoinflammatory syndromes that are considered to be rare entities. CASE REPORTS: The authors describe the clinical features of three patients whose diagnosis were the following: tumor necrosis factor receptor-associated periodic syndrome (TRAPS), chronic infantile neurological cutaneous articular (CINCA) syndrome and familial Mediterranean fever (FMF). All of the patients presented fever, joint or bone involvement and increased acute phase reactants. The genetic analysis confirmed the diagnoses of two patients. The great diversity of manifestations and the difficulties in genetic analyses make the diagnosing of these diseases a challenge.